Seleniferous soils: Spatial distribution, impact on plant, human and animal health, and its management - Jaidka, Manpreet; Singh, Jugraj; Kaur, Ramanjit; Dass, Anchal (Indian Farming, 2018)
Selenium (Se) does not act as an essential element in plant growth and development yet its existence in food and fodder is important for animal and human health. Soils with highly elevated Se concentrations (>2–5000 mg/kg) called seleniferous soils, are widely distributed throughout the world. Several regions throughout the world are known to suffer from Se intoxication due to consumption of food and forage grown on seleniferous soils. Pockets of seleniferous soils have also been identified in India especially in the North-eastern parts of Punjab and Haryana. The Se concentration in soils is mainly determined by the Se content of the parent rock, the topography and the climate, but several other factors can considerably enhance the soil Se content. In agricultural crops, symptoms of selenium toxicity include loss of chlorophyll, whitening of leaves, stunting of plants etc. In wheat crop, whitening of leaves also include pinkish coloration in lower-side of leaves. In humans, regular consumption of cereals grown in these soils results in the visible symptoms like cracked and discolored nails. Other symptoms include loss of body hairs, bleeding from the nails and gradual loss of health. The fodders grown on these soils may prove fatal for the domestic animals which can lead to mortality.